How to sustain interprofessional learning and practice: Messages for higher education and health and social care management - Meads, G.; Jones, I.; Harrison, R.; Forman, Dawn; Turner, W. (Routledge, 2009)
The principal aim of this article is to promote the more effective integration of interprofessional learning with practice developments in health and social care. Ten specific recommendations are offered for the successful management of recent central policies for collaboration at the interface of the higher education and service sectors. Presented in an 'Ideal Type' format they are derived from four qualitative studies linked to the evaluation during 2004-08 of the NHS 'Creating an Interprofessional Workforce' programme. These include an international literature review, semi-structured interviews with a representative sample of higher education leaders, participant observation in local projects and focus groups. The research findings also indicated the need for central policy-makers to take more account of both enabling cultural influences when seeking sustainable change and the new opportunities for integration that arise from the growth of Third Sector agencies in health and social care.